Literature Review: Potensi Senyawa Bahan Alam Sebagai Inhibitor A-Glukosidase Untuk Terapi Diabetes Melitus Melalui Pendekatan Molecular Docking - Asti Awaliyah Weguna; Saeful Amin (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Type 2 diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels due to insulin resistance. One effective therapeutic strategy is the inhibition of the ?-glucosidase enzyme, which plays a crucial role in carbohydrate breakdown into glucose. This study aims to review the potential of natural compounds as ?-glucosidase inhibitors for diabetes therapy through a molecular docking approach. Literature searches were conducted through PubMed, ScienceDirect, and Google Scholar databases (2020–2025), and eight eligible articles were analyzed. The results revealed that orientin, vitexin, and reserpine from Sonneratia alba, pimaric acid from Michelia champaca, mimopudine from Mimosa pudica, apigenin from Psidium guajava, and spirost-8-en-11-one from Momordica charantia exhibited stronger binding affinities than acarbose. Their interactions with key catalytic residues (Asp215, Glu277, His351, and Asp542) indicate a strong inhibitory potential against ?-glucosidase. These findings suggest that flavonoids, alkaloids, and triterpenoids from medicinal plants possess significant potential as natural ?-glucosidase inhibitors that are safer and more effective. Further in vitro and in vivo studies are recommended to validate their pharmacological activity and safety prior to clinical application.